The shield of Homer : narrative structure in the Iliad - Stanley, Keith, 1934- (Princeton legacy library., 1993)
In this masterly interpretation of narrative sequence in the Iliad, Keith Stanley not only sharpens the current debate over the date and creation of the poem, but also challenges the view of this work as primarily a celebration of heroic force. He begins by studying the intricate ring-composition in the verses describing Achilles' shield, then extends this analysis to reveal the Iliad as an elaborate and self-conscious formal whole.